Report of the Technical Team on the Long Term and Short Term Plan for Nagaland - Planning Commission (Planning Commission, 1966)
The State of Nagaland was formed on 1st December, 1963 under the State of Nagaland Act 1962 and is the sixteenth State within the Indian Union. Nagaland includes the former Naga Hills districts of Assam and the Tuensang Division of the North East Frontier Agency and is divided into three districts of Kohima, Mokokchung and Tuensang.
Planning Commission Government of India
Planning Commission Government of India